A Novel Synthesis Method of Porous Calcium Silicate Hydrate Based on the Calcium Oxide/Polyethylene Glycol Composites. (23rd October 2013) - Guan, Wei; Ji, Fangying; Cheng, Yong; Fang, Zhuoyao; Fang, Dexin; Yan, Peng; Chen, Qingkong
Abstract : This paper proposed a novel method to prepare porous calcium silicate hydrate (CSH) based on the calcium oxide/polyethylene glycol (CaO/PEG2000 ) composites as the calcium materials. The porosity formation mechanism was revealed via X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET), and Fourier transformed infrared spectroscopy (FT-IR). The reactivity of silica materials (SiO2 ) enhanced by increasing pH value. Ca 2+ could not sustain release from CaO/PEG2000 and reacted with SiO 3 2 − caused by silica to form CSH until the hydrothermal temperature reached to 170°C, avoiding the hardly dissolved intermediates formation efficiently. The as-prepared CSH, due to the large specific surface areas, exhibited excellent release capability of Ca 2+ and OH − . This porous CSH has potential application in reducing the negative environmental effects of continual natural phosphate resource depletion.